The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/apm.12858
|View full text |Cite
|
Sign up to set email alerts
|

Re‐view and view on maturation disorders in the placenta

Abstract: Until delivery, the placenta plays an important mediator role between mother and fetus. This unit is affected by peristatic conditions, such as acute or chronic maternal diseases, malnutrition, drugs, and others. But also genetic factors and fetal malformations due to embryonic developmental disorders may contribute to macroscopically visible changes and functional disorders of the placenta. In a constantly ongoing progress of maturation, the placenta records and saves changes due to fetal distress partly as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…In our study we found a significantly higher proportion of cases with RPH. Malperfusion can lead to changes such as AVM and subsequent DVH due to a poorly developed distal villous tree [8]. Both these findings were significantly higher in cases.…”
Section: Discussionmentioning
confidence: 91%
“…In our study we found a significantly higher proportion of cases with RPH. Malperfusion can lead to changes such as AVM and subsequent DVH due to a poorly developed distal villous tree [8]. Both these findings were significantly higher in cases.…”
Section: Discussionmentioning
confidence: 91%
“…), blind to case or control status, gestational age and maternal characteristics. The classification of any histological features was performed according to previous agreed and standardized criteria (Table 3) (Redline, 2015; Turowski & Vogel, 2018). Pathological features were recorded qualitatively (present or absent).…”
Section: Methodsmentioning
confidence: 99%
“…This is a placental histopathologic finding that can be found near the end of pregnancy and rarely before 34 weeks of gestation [24]. It is clinically associated with FGR as well as intrauterine hypoxia, maternal metabolic disorder, and obesity [68]. It is characterized by a monotonous unvaried villous population, with increased villous diameter, with centrally placed capillaries, cellular stroma, a continuous cytotrophoblast l ayer, and reduced numbers of vasculosyncytial membranes [24].…”
Section: Placenta In Late Fgrmentioning
confidence: 99%